2021
DOI: 10.3847/1538-4357/abd5be
|View full text |Cite
|
Sign up to set email alerts
|

Planets Across Space and Time (PAST). I. Characterizing the Memberships of Galactic Components and Stellar Ages: Revisiting the Kinematic Methods and Applying to Planet Host Stars

Abstract: Over 4000 exoplanets have been identified and thousands of candidates are to be confirmed. The relations between the characteristics of these planetary systems and the kinematics, Galactic components, and ages of their host stars have yet to be well explored. To address these questions, we conduct a research project, dubbed Planets Across Space and Time (PAST). To do this, one of the key steps is to accurately characterize the planet host stars. In this paper, Paper I of the PAST series, we revisit the kinemat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 90 publications
2
34
1
Order By: Relevance
“…We can also see in the figure that there are stars that have chemical abundances suggesting that they are from the thick disc and yet have stellar velocities similar to that of thin-disc stars. Ho we ver, past surv e ys hav e also shown that galactic thick-disc stars will often hav e similar kinematics to those stars found in the thin disc (Kov ale v et al 2019 ;Chen et al 2021 ).…”
Section: Searching For Thick-disc Hosts Within Galahmentioning
confidence: 64%
See 1 more Smart Citation
“…We can also see in the figure that there are stars that have chemical abundances suggesting that they are from the thick disc and yet have stellar velocities similar to that of thin-disc stars. Ho we ver, past surv e ys hav e also shown that galactic thick-disc stars will often hav e similar kinematics to those stars found in the thin disc (Kov ale v et al 2019 ;Chen et al 2021 ).…”
Section: Searching For Thick-disc Hosts Within Galahmentioning
confidence: 64%
“…Due to the complex and non-linear nature that the chemical, kinematic, and dynamic information that stars have with their associated stellar groups, we leave the rest to be characterized in further studies. Having a homogeneous and more inclusive sample of thick-disc stars, such as Chen et al ( 2021 ) and others, would allow exoplanetary scientists to better probe the characteristic planetary population differences between the stellar populations, leading on to implications for astrobiology and habitability across the Milky Way (Santos et al 2017 ).…”
Section: Star Namementioning
confidence: 99%
“…We can also see in the Figure, that there are stars that have chemical abundances suggesting that they are from the thick-disc, yet have stellar velocities similar to that of thin disk stars. However, past surveys have also shown that galactic thick-disc stars will often have similar kinematics to those stars found in the thin-disc (Chen et al 2021;Kovalev et al 2019).…”
Section: Searching For Thick-disc Hosts Within Galahmentioning
confidence: 92%
“…Due to the complex and non-linear nature that the chemical, kinematic and dynamic information that stars have with their associated stellar groups, we leave the rest to be characterised in further studies. Having a homogeneous and more inclusive sample of thick-disc stars, such as Chen et al (2021) and others, would allow exoplanetary scientists to better probe the characteristic planetary population differences between the stellar populations, leading onto implications for astrobiology and habitability across the Milky Way (Santos et al 2017).…”
Section: Searching For Thick-disc Hosts Within Galahmentioning
confidence: 99%
“…Towards a Galactic census of planets, we have started a research project, dubbed Planets Across Space and Time (PAST). In the Paper I (here after PAST I, Chen et al 2021) of the PAST series, we revisited the kinematic methods for classification of Galactic components and extended the applicable range of the methods from ∼ 100 − 200 pc to ∼ 1.5 kpc to cover most of planet candidate host stars. Additional, we revised the Age-Velocity dispersion Relation (AVR), which allows us to derive kinematic age with a typical uncertainty of ∼ 10 − 20% for an ensemble of stars.…”
Section: Introductionmentioning
confidence: 99%